Hubungan Faktor Kualitas Lingkungan Rumah Dengan Kejadian Pneumonia Pada Bayi di Wilayah Kerja Puskesmas Banjarmangu 1 Kabupaten Banjarnegara. - Juni, Masfufatun; Nurjazuli, Nurjazuli; Suhartono, Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Background: Pneumonia is an infectious disease remains a public health problem in Indonesia. Pneumonia is a disease of the second highest cause of death after diarrhea. This can be seen in the proportion of pneumonia in infant and toddler around 35%. In the working area of Banjarmangu 1, the number of infant affected by pneumonia were 112 among 417 infants. The proportion of healthy house is still low (27.15%) of the target of 80%. Based on this facts, the purpose of this study was to determine the correlation between the quality of the house environment factor with the incidence of pneumonia in infant in the working area community health center Banjarmangu 1 Banjarnegara.Methods: This study was observational study with case control design. The subjects consisted of two groups of case and control, with each sample of 52 infants. The independent variables studied were the type of wall, floor type, ceiling presence, expansive windows / ventilation, natural lighting, residential density, number of bacteria, the intensity of temperature, light intensity and the intensity of moisture, while the dependent variable was the incidence of pneumonia. Data was collected through interviews, observation, and measurement. Data would be analyzed using univariate, bivariate chi-square, and multivariate logistic regression at level of significance 0.05 (5%).Results: Bivariate analysis of 10 variables are the type of wall, floor type, ceiling presence, wide window / ventilation, natural lighting, residential density, number of bacteria, the intensity of the temperature, humidity and intensity of light intensity, indicated that there were two variables that have a correlation with incidence of pneumonia in infant. They were the type of wall and ceiling existence. Results of multivariate analysis that kind of wall is the most dominant factor related to the incidence of pneumonia in infant with p-value = 0.004; OR = 6.6 (1.79 - 24.57).Conclusion: This study concluded that the quality of the house environment conditions was still need to be improved, especially the type of wall and ceiling existence. This is to reduce the incidence of pneumonia in infant.